AN INDOCHINESE VICHY SYNDROME?: Remembering and Forgetting World War II Indochina. Issue 2 (1st July 2019) - Edwards, M. Kathryn; Jennings, Eric
Abstract : This article analyzes the complex memorial stakes of the events that unfolded in French Indochina during World War II. It first considers the wartime years and analyzes the French frameworks for understanding the Vichy period and the Japanese takeover. It then delves into two memorial trends: the rehabilitation of the French resistance in Indochina and the commemoration of victims of the 9 March 1945 Japanese coup. These trends have produced a double elision: the focus on resistance to the Japanese has displaced previous allegiance to Vichy, and the emphasis on the victimhood of the French settler community has overshadowed responsibility for colonial violence.